Increasing Student’s Ability to Write Descriptive Text Using the Brainstorming Method - Wahyu Sudrajad; Sulistyaningsih Sulistyaningsih; Fitria Ulfa (International Journal of English and Applied Linguistics (IJEAL), 2023)
The focus of this research was on the problems and difficulties faced by students when they were writing descriptive text. The aim of this study was to improve student’s ability in writing descriptive text using brainstorming method. The subjects of this study were20 students of VII B of Jati Agung Junior High School participated as the subject of the study. The method used was classroom action research contained four components: planning, acting, watching, and reflecting. The instrument used for data collection were test and observation field notes. The findings of this study were two cycles. In the cycle 1, the students pre-test scores resulted in only 10% or two students passed standard criteria minimum score, and the post-test resulted 40% or four students passed standard minimum score criteria. While in the cycle 2 students gained 70% or 14 students passed standard minimum score (M>75). In conclusion it be able that the brainstorming method can be used to improve the student’s ability in writing descriptive text.